2014
DOI: 10.1038/sj.bdj.2014.702
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and post-operative management of dental implant placement. Part 2: management of early-presenting complications

Abstract: Despite morbidity factors that include pain and complications with healing, there is currently little available guidance regarding optimal pre-and post-operative protocols for dental implant placement. While the first paper of this two-part series discussed the management of post-operative pain, the second instalment reviews pre- and post-operative means of managing early complications associated with dental implant placement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 64 publications
0
12
0
1
Order By: Relevance
“…With respect to dental implants, chlorhexidine has indications at several different stages: Pre-surgical mouth rinse (0.12% or 0.2% Chlorhexidine) to reduce oral microbial load for 7-10 days prior to surgery and immediately prior to surgery [ 64 , 65 ]; Post-operative protocols involving application of pressure for 30 minutes with gauze soaked in chlorhexidine [ 65 ] and rinse and during 7-14 days after surgery to aid healing [ 66 , 67 ] and for treatment of post-operative infections; Reduction of implant biofilm formation post-surgery [ 68 ] this may not necessarily relate to long improved outcomes in terms of preventing or managing longer term infections such as peri-implantitis As a mouth rinse during implant maintenance and for treatment of peri-implant disease, where high levels of plaque control are important. Including, irrigation with 0.12-0.2% chlorhexidine, plus topical chlorhexidine gel for 10 days, as an adjunct to mechanical debridement, may be beneficial [ 69 ].…”
Section: Uses For Oral Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…With respect to dental implants, chlorhexidine has indications at several different stages: Pre-surgical mouth rinse (0.12% or 0.2% Chlorhexidine) to reduce oral microbial load for 7-10 days prior to surgery and immediately prior to surgery [ 64 , 65 ]; Post-operative protocols involving application of pressure for 30 minutes with gauze soaked in chlorhexidine [ 65 ] and rinse and during 7-14 days after surgery to aid healing [ 66 , 67 ] and for treatment of post-operative infections; Reduction of implant biofilm formation post-surgery [ 68 ] this may not necessarily relate to long improved outcomes in terms of preventing or managing longer term infections such as peri-implantitis As a mouth rinse during implant maintenance and for treatment of peri-implant disease, where high levels of plaque control are important. Including, irrigation with 0.12-0.2% chlorhexidine, plus topical chlorhexidine gel for 10 days, as an adjunct to mechanical debridement, may be beneficial [ 69 ].…”
Section: Uses For Oral Diseasementioning
confidence: 99%
“…Pre-surgical mouth rinse (0.12% or 0.2% Chlorhexidine) to reduce oral microbial load for 7-10 days prior to surgery and immediately prior to surgery [ 64 , 65 ];…”
Section: Uses For Oral Diseasementioning
confidence: 99%
“…In our study, bone quality was assessed as being similar to mature bone 4-6 months after implant placement at all implant sites. Considering dental implant surgery can be associated with complications leading to patient morbidity and implant failure (5,6,43) including peri-implantitis in 34% of cases (44) and flap dehiscence in 19.1% (45), our preliminary result of the clinical study is encouraging. We have seen no complications and successful restoration of bone tissue in GBR by CelGro™ in 16 implants among 10 participants…”
Section: Discussionmentioning
confidence: 79%
“…Type I collagen is major protein component of the ECM in bone. It has been shown that undenatured type I collagen has a dynamic, bioactive structure with the ability to regulate cellular proliferation, differentiation and repair (43,44). We showed that CelGro™ is a predominantly Type I collagen bilayer membrane with two distinct sides of differently-aligned collagen fibers.…”
Section: Resultsmentioning
confidence: 99%
“…It has been recommended that the anti-bacteria treatment could be performed in the event compromised local and systematic conditions increase the infection possibility of the implantation sites. [21][22][23] We expect that this modied abutment might be used immediately aer implant placement as a prophylaxis treatment, in patients with complex bone augmentation, at susceptible sites of an immediately placed implant, suffering from previous periodontitis or periapical lesion, or compromised systematic conditions (such as diabetes). Thus, the special healing abutment might play a role in the prevention of peri-implantitis and early infection.…”
Section: Discussionmentioning
confidence: 99%